Left Ventricular Diastolic Dysfunction in Liver Cirrhotic Patients: Proportion, Correlation, and Relationship of Diastolic Parameters with Stage of Liver Dysfunction - Mondrowinduro, Prionggo; Hasan, Irsan; Alwi, Idrus; Abdullah, Murdani (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. Cardiovascular complication of liver cirrhosis is relatively obscure. Pathophysiology of liver cirrhosis, involving portal hypertension made the possibility of cirrhosis complication manifested as left ventricular diastolic dysfunction. This study aims to determine proportion of left ventricular diastolic dysfunction among liver cirrhotic patients according to American Society of Echocardiography-European Association of Echocardiography (ASE-EAE) 2009 and conventional approach, to determine any correlation between left ventricular diastolic dysfunction severity stages with severity stages of liver dysfunction in cirrhotic patients represented by Child Turcotte Pugh (CTP ) score, also to asses relationship between severity stages of parameters of diastolic function according to ASE-EAE 2009 with liver cirrhosis severity evaluated by numerical CTP score. Methods. A cross sectional study was conducted among 96 liver cirrhotic patients within age of 18-60 years old consecutively due to any causes who admitted to ambulatory unit of Hepatology and Internal Medicine Cipto Mangunkusumo General Hospital wards into intended sample. The study started in November 2013 until proper sample size was obtained. Echocardiography examination was performed by two operators. Interobserver validity was assesed with level of Kappa aggrement and mean difference. Data were extracted to determine prevalence, normality test, Spearman correlation test, and multivariate linear regression test using SPSS for Windows. Results. Left ventricular diastolic dysfunction proportion among liver cirrhotic patients according to ASE-EAE 2009 was 34,3% and 21,9% of normal diastolic function subgroup has left atrial volume index ≥34 mL/m2. Meanwhile, conventional approach resulted in 68,8% of diastolic dysfuncation. All diastolic parameter showed abnormalities on CTP B 8-10. Spearman’s r values of stage of diastolic dysfunction severity according to ASE-EAE 2009 with severity of numerical CTP score was 0,42 (p<0,001) and 0,54 based on conventional approach. Exclusion of diabetic patients and spironolactone treated patients resulted in r=0,51 (p <0,001) based on ASE-EAE 2009 and 0,63 (p<0,001) based on conventional approach.. Parameters of diastolic function that had relation with liver dysfunction severity in cirrhosis measured by numerical CTP were Ar-A (p=0,004), left atrial volume index (p=0,005), and laterale e’ (p=0,026). Conclusion. Severity of left ventricular diastolic dysfunction with severity of liver cirrhosis is positively correlated. Diastolic parameters relate with severity of liver cirrhosis are diastolic ventricular filling pressure with left ventricular chamber stiffness, left atrial remodelling and regurgitant of pulmonary venous flow velocity to oppose filling pressure. Early detection for diastolic dysfunction can be started on CTP B 8. Keywords: Child Turcotte Pugh Score, diastolic dysfunction, liver cirrhosis, liver dysfunction